Inﬂuence of Land Use Patterns in the Quality of Surface Waters of the Virilla River Sub-Basin, Costa Rica - Herrera-Murillo, Jorge (2019)
We analyzed the relation between land use patterns and chemical quality of surface water bodies that make up the sub-basin of the Virilla River, Costa Rica. For this purpose, a total of 64 monitoring sites were selected, distributed in the 15 micro-basins that make up the sub-basin, where a total of four samples were drawn between November 2014 and December 2015. The following parameters were analyzed for the samples collected: Hydrogen potential (pH), conductivity, turbidity, total suspended solids (TSS), sedimentary solids, Biochemical Oxygen Demand (BOD), Chemical Oxygen Demand (COD), ammonium (NH4+), nitrite (NO2-), nitrate (NO3-), total nitrogen, chloride (Cl-), sulfate (SO42-), sodium, calcium, potassium, magnesium, aluminum, iron, manganese, copper, chromium, nickel, zinc, lead, total phosphorus, dissolved oxygen and temperature.  Cluster analysis, based on the results of chemical analyses of surface water samples, showed that the 15 micro watersheds could be grouped into six clusters, where groups I-IV showed a greater contribution of pollutants derived from the discharge of wastewater from urbanized areas. The Spearman correlation study revealed that, with increasing urbanization, the pollutant load of COD, BOD, TSS, NH4+, and NO2- in rivers increased, compared to those where agricultural land and forest use predominate.